2015
DOI: 10.1007/s12016-015-8505-8
|View full text |Cite
|
Sign up to set email alerts
|

T and NK Cell Phenotypic Abnormalities in Systemic Sclerosis: a Cohort Study and a Comprehensive Literature Review

Abstract: Scleroderma (SSc) is a rare and heterogeneous immune-mediated disease involving the connective tissue and microvasculature whose pathogenesis remains unclear. Data concerning T and natural killer (NK) cell abnormalities and cytokine levels in the peripheral blood (PB) from patients with SSc are scarce, and the results are contradictory. The present study aimed to analyze the changes of T lymphocytes, NK cells, and T helper (Th)-related cytokines in the PB of patients with SSc in comparison to healthy individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 108 publications
5
28
1
Order By: Relevance
“…Here we applied CYTOF to directly compare different SADs in an attempt to dissect both distinct and overlapping patterns of circulating immune cells thereby aiming at molecular classification of SADs rather than on their diagnostic vignettes. Our results confirmed recent observations in patients with pSS by Mingeneau et al, as well as a previously observed decrease of CD56 + NK-cells in SSc patients [8][9][10]. In addition, we identified both overlapping and distinct immune cell phenotypic alterations among patients with SSc, SLE, and pSS.…”
Section: Introductionsupporting
confidence: 92%
“…Here we applied CYTOF to directly compare different SADs in an attempt to dissect both distinct and overlapping patterns of circulating immune cells thereby aiming at molecular classification of SADs rather than on their diagnostic vignettes. Our results confirmed recent observations in patients with pSS by Mingeneau et al, as well as a previously observed decrease of CD56 + NK-cells in SSc patients [8][9][10]. In addition, we identified both overlapping and distinct immune cell phenotypic alterations among patients with SSc, SLE, and pSS.…”
Section: Introductionsupporting
confidence: 92%
“…In Sjögren's syndrome, this subset is also increased, regardless of disease activity (44). In contrast, circulating CD56 bright NK cells are decreased in juvenile dermatomyositis (45) and in systemic sclerosis (46).…”
Section: Cd56mentioning
confidence: 99%
“…Regarding autoimmune diseases, patients suffering from systemic sclerosis, mainly those with active/late capillaroscopic patterns or with severe lung impairment, have decreased numbers of circulating CD56 + CTLs as compared to healthy individuals (60). Even though different mechanisms may be involved, this decline in CD56 + T cells in the peripheral blood results at least in part from the recruitment and/or trafficking of these cells to the affected tissues, where they cause endothelial cell injury and apoptosis (32).…”
Section: Cd56 Expression On Human Immune Cells In Health and Diseasementioning
confidence: 99%